Hepatitis C virus and hepatocellular carcinoma: carcinogenesis in the era of direct-acting antivirals - Fiehn, Felix; Beisel, Claudia; Binder, Marco (Current opinion in virology, 2024)
Chronic hepatitis C virus (HCV) infection is a major cause of hepatic fibrosis and cirrhosis, with a risk for the development of hepatocellular carcinoma (HCC). Although highly effective direct-acting antivirals (DAAs) are available, the incidence, morbidity, and mortality of HCV-associated HCC are still high. This article reviews the current knowledge of the mechanisms of HCV-induced carcinogenesis with a special focus on those processes that continue after virus clearance and outlines implications for patient surveillance after DAA treatment.
Online verfügbar 25 June 2024, Version des Artikels 25 June 2024
Gesehen am 16.12.2024